PENEGAKAN HUKUM OLEH HAKIM AGUNG REPUBLIK INDONESIA DALAM MENANGANI KASASI PERKARA KARTEL PUTUSAN KPPU YANG MENGGUNAKAN ALAT BUKTI TIDAK LANGSUNG (INDIRECT EVIDENCE) - Fransiska Lestari Simanjuntak (Madani Legal Review, 2019)
Business Competition Supervisory Commission (KPPU) is an institution authorized to handle unfair business competition violation. In fact, in several KPPU decisions it was revealed that KPPU prioritizes indirect evidence in handling cartel cases in Indonesia. KPPU's decision is not final and binding. Business actors who do not accept the decision of KPPU may file an objection at the District Court. The parties who do not accept the decision of the district court, may file an appeal in the Supreme Court of the Republic of Indonesia. The type of research is used in this research is normative legal research, that is research done by reviewing the rules of law applicable or applied to a certain legal problem. The result of the research shows that in the Supreme Court appeal, KPPU's decision was upheld and canceled by Supreme Court to KPPU's decision uses indirect evidence in handling cartel case. The basis of consideration of the Supreme Court Justices ruling the KPPU's decision in the case of the tire cartel and the cement cartel is the Chief Justice accepting and acknowledging the indirect evidence as valid evidence, since the evidence is sufficient and logical evidence, and there is no evidence the more powerful that can weaken the indirect evidence. While the consideration of the Supreme Court Judge overturning the KPPU's decision in the case of cartel fuel surcharger is not accepting and acknowledging indirect evidence as valid evidence, because the evidence is insufficient and illogical, and there is stronger evidence that can weaken the tool indirect evidence